Can Ultrasound of the Tibial Nerve Detect Diabetic Peripheral Neuropathy?: A cross-sectional study - RIAZI, Sheila; BRIL, Vera; PERKINS, Bruce A; ABBAS, Sherif; CHAN, Vincent W. S; NGO, Mylan; LOVBLOM, Leif E; EL-BEHEIRY, Hossam; BRULL, Richard (Diabetes care, 2012)
Peripheral nerve imaging by portable ultrasound (US) may serve as a noninvasive and lower-cost alternative to nerve conduction studies (NCS) for diagnosis and staging of diabetic sensorimotor polyneuropathy (DSP). We aimed to examine the association between the size of the posterior tibial nerve (PTN) and the presence and severity of DSP. We performed a cross-sectional study of 98 consecutive diabetic patients classified by NCS as subjects with DSP or control subjects. Severity was determined using the Toronto Clinical Neuropathy Score. A masked expert sonographer measured the cross-sectional area (CSA) of the PTN at 1, 3, and 5 cm proximal to the medial malleolus. Fifty-five patients had DSP. The mean CSA of the PTN in DSP compared with control subjects at distances of 1 (23.03 vs. 17.72 mm(2); P = 0.004), 3 (22.59 vs. 17.69 mm(2); P < 0.0001), and 5 cm (22.05 vs. 17.25 mm(2); P = 0.0005) proximal to the medial malleolus was significantly larger. Although the area under the curve (AUC) for CSA measurements at all three anatomical levels was similar, the CSA measured at 3 cm above the medial malleolus had an optimal threshold value for identification of DSP (19.01 mm(2)) with a sensitivity of 0.69 and a specificity of 0.77 by AUC analysis. This large study of diabetic patients confirms that the CSA of the PTN is larger in patients with DSP than in control subjects, and US is a promising point-of-care screening tool for DSP.